Estimation of cross section for proton induced reactions in stable Yb isotopes at astrophysical energies. - Nikou, Danai Paraskevi; Archontovasilis, Philip; Mertzimekis, Theodoros (HNPS Advances in Nuclear Physics, 2026)
In this work, we address a piece of an open problem in nuclear astrophysics: the synthesis of elements heavier than iron. While the formation of light elements up to iron is well understood, the origin and abundance of heavier nuclei, particularly those with atomic mass number A>56, remain under investigation. Among the proposed mechanisms, proton-capture reactions play a central role for p-nuclei, especially in extreme astrophysical environments. In this study, we focus on the theoretical modeling of proton-capture reactions on stable isotopes of Ytterbium (Yb). Although Yb is not a p-nucleus itself, its isotopes (168Yb to 176Yb) are relevant to understanding nucleosynthesis pathways near the limits of stability. Due to the scarcity of experimental cross-section data in the energy range of 1–8 MeV, we have employed the Hauser-Feshbach model to simulate (p,γ) reactions and extract cross section values and the astrophysical S-factor, running TALYS v2.0 with various parameter options. Our main motivation is two-fold: first, to prepare the grounds for experimental work in this series of isotopes at such low energies, and second, improve our understanding of heavy element formation via the proton-capture process in an energy region, where the high Coulomb barrier works as an impeding factor.